Dual hollow sphere optical resonator for simultaneous detection of acoustic and magnetic fields - Feng, Chaoyu; Yu, Changqiu; Hu, Yuchi; Chang, Jian; Hou, Pei; Li, Hai; Guo, Ying (Frontiers in Physics, 2025)
This study introduces a novel dual-parameter sensor for simultaneous acoustic and magnetic field detection. The sensor employs a dual-hollow-sphere-shaped optical microresonator coupled with a fiber taper and integrated with a Terfenol-D sheet. Experimental results demonstrate best sensitivities of 4.24 mPa/√Hz for acoustics and 5.16 nT/√Hz for magnetic fields within a 0.1–2 MHz detection range. Notably, the sensor can detect both parameters independently at different frequencies without mutual interference. This innovative design offers a promising approach for non-destructive testing of the state of the high-voltage transmission lines.